2004
DOI: 10.1002/mrd.20157
|View full text |Cite
|
Sign up to set email alerts
|

Vitellogenin mRNA expression in Cherax quadricarinatus during secondary vitellogenic at first maturation females

Abstract: PCR products of 1.1 and 0.9 kb were generated using Cherax quadricarinatus genomic DNA in the first case, and hepatopancreas and ovary cDNAs in the second case. These PCR products were cloned and analyzed for nucleotide sequences. The 1.1 kb fragment was used as a probe for Northern hybridization, revealing a transcript of approximately 8 kb in both tissues. Results from both Northern blot and RT-PCR analyses showed that the mRNA enconding the 3' end of the vitellogenin cDNA was present simultaneously in both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…3). Multiple Vg genes have been identified in C. quadricarinatus (Serrano-Pinto et al, 2004) where two Vg cDNAs have been isolated. In the shrimp, Mentapenaeus ensis, there are four Vg genes predicted, two of which have been cloned (Tsang et al, 2003).…”
Section: Possible Second Vgmentioning
confidence: 99%
See 1 more Smart Citation
“…3). Multiple Vg genes have been identified in C. quadricarinatus (Serrano-Pinto et al, 2004) where two Vg cDNAs have been isolated. In the shrimp, Mentapenaeus ensis, there are four Vg genes predicted, two of which have been cloned (Tsang et al, 2003).…”
Section: Possible Second Vgmentioning
confidence: 99%
“…The site of Vg RNA synthesis in the Crustacea is in dispute. In some Custacea, the main Vg source is the hepatopancreas (Tseng et al, 2001;Lee and Chang, 1999;Okuno et al, 2000) while in others the ovary also produces vitellogenin (Serrano-Pinto et al, 2004;Avarre et al, 2003;Pateraki and Stratakis, 2000). In the shrimp, Metapenaeus ensis, Vg is encoded by at least two genes, one expressed in both the hepatopancreas and ovary and the other in the hepatopancreas only (Tsang et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…A similar response was reported by FERREIRA et al (2005) studying A. platensis fed for 15 days on a high-carbohydrate or highprotein diet in controlled laboratory conditions. Several studies have evaluated maturation, eye ablation (SAGI et al, 1997;WONGPRASERT et al, 2006), use of hormones (ABDU et al, 2001), fecundity (KING, 1993), and reproductive cycle (SERRANO-PINTO et al, 2004) of the redclaw crayfish under laboratory conditions. Different diets have been used in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…The yolk mainly consists of vitellin, a lipoglyco-carotenoprotein, which in Cherax quadricarinatus is composed of subunits of 75-177 kDa (Khalaila et al, 2004). Serrano-Pinto et al (2004) found in the same species two vitellins with native molecular masses of 440 and 470 kDa. The oocytes are apparently able to synthesize yolk from primary vitellogenesis ( fig.…”
Section: Reproductive Systemmentioning
confidence: 98%
“…67.15C) until ovulation, but during secondary vitellogenesis yolk precursors, the vitellogenins, are additionally produced in the hepatopancreas, secreted into the hemolymph, transported to the ovary, absorbed by the follicle cells, and transferred to the oocytes (Abdu et al, 2002;Vogt, 2002;Serrano-Pinto et al, 2004). Serrano-Pinto et al (2004) analysed the cDNAs from the hepatopancreas and ovary of Cherax quadricarinatus and found that there are at least two different vitellogenin genes. It is not known whether the follicle cells serve only for transcytosis of the vitellogenins or whether they participate in their processing.…”
Section: Reproductive Systemmentioning
confidence: 99%